Biodegradable polymers as carriers for tuning the release and improve the herbicidal effectiveness of Dittrichia viscosa plant organic extracts. Issue 2 (22nd October 2020) - Serino, Nadia; Boari, Angela; Santagata, Gabriella; Masi, Marco; Malinconico, Mario; Evidente, Antonio; Vurro, Maurizio
Abstract: BACKGROUND: The organic extracts (OEs) of Dittrichia viscosa, a ruderal plant common in the Mediterranean regions, proved to have herbicidal properties. In order to improve OE effectiveness and to develop novel eco‐friendly bioherbicidal products, different amounts of OE were included in poly(butylene succinate)‐ and polycaprolactone‐based films (PBS and PCL, respectively). Particular attention was given to the study of interactions between the polymers and OEs, with a deep spotlight concerning the influence of OEs on structural, morphological and thermal properties of both polymers, in order to assess the OE releasing kinetics from the matrices and its tuned herbicidal action against seeds. RESULTS: The bioassays carried out on Lepidium sativum and Phelipanche ramosa seeds evidenced a more controlled and effective OE release by PBS than PCL, and a longer lasting efficacy by the polymers with a higher OE content. The chemical–physical analyses were performed on films before and after biological assays. The thermogravimetric analysis confirmed that OE was a thermal stabilizer of the polymer; the presence of OE and polymer separated degradative kinetics suggested that only a partial and functional miscibility between polymers and OE occurred. The morphological analysis confirmed the good OE dispersion between PBS and PCL molecular chains. Infrared spectroscopy highlighted the enhanced hydrolysed structure of the doped polymers after the bioassays. These outcomes well matched the quantitative information outlined by release kinetics. DISCUSSION: The use of biodegradable polymers allows the effectiveness and tuning of the release of the formulated bioactive compounds to be improved. The easy‐to‐obtain and easy‐to‐formulate OE could become a suitable and environmentally friendly instrument in weed management programmes. Abstract : The use of biodegradable polymers allowed the herbicidal effectiveness and tuning of the release of the formulated bioactive extract obtained by Dittrichia viscosa plants to be improved. © 2020 Society of Chemical Industry